PEMANFAATAN TUMBUHAN TESPONG (OENANTHE JAVANICA DC), SINTRONG (CRESSOCEPHALUM CREPIDIOIDES ), DAN POHPOHAN (PILEA TRINERVIA W) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI STAPHYLOCOCCUS EPIDERMIDIS & PSEUDOMONAS AERUGENOSAE - Roni, Asep (Journal of Pharmacopolium, 2018)
Tespong (Oenanthe javanica), sintrong (Crassocephalum crepidioides), and pohpohan (Pilea trinervia) is a type of indigenous vegetables which have antibacterial activity and consumed by Indonesian people, especially people of West Java. The study was conducted to determine the most powerful antibacterial activity among leave extracts of tespong, sintrong, and pohpohan and also to determine the active compound that responsible for inhibiting Staphylococcus epidermidis and Pseudomonas aeruginosa bacteria. The extraction was done by maceration method using ethanol 96% solvent. Antibacterial activity test was conducted by microdilution method and using tetracycline as a comparison. The measured parameters was the Minimum Inhibitory Concentration (MIC). The highest antibacterial activity was pohpohan leaf extract with MIC values of 640 mg/mL againts Staphylococcus epidermidis and 1280 mg/mL againts Pseudomonas aeruginosa, as well as n-hexane fraction of pohpohan with MIC 1280 ug/mL inhibit Staphylococcus epidermidis and MIC values of 2560 mg/mL inhibit Pseudomonas aeruginosa. The results of bioautography test of n-hexane fraction showed the content of flavonoid which was suspected as the active antibacterial..